Eskalasi Mutu Pendidikan Indonesia dalam Fomo Perkembangan Kecerdasan Buatan : Escalation of The Quality of Indonesian Education in The Fomo Of Artificial Intelligence Development - Arya Bagus Nur Ajiyanto; Safinatunnajah; Hanan Nur Faridah (Al-Absah: Journal of Civilization, Language, Literature, and History, 2025)
The escalation of the quality of education in Indonesia is currently undergoing a significant transformation along with the development of artificial intelligence (AI), as well as the rapid development of social media technology, or commonly referred to as Edu-Content. The application of AI and Edu Content technology in education provides opportunities for the development of learning methods that are more innovative, effective, and quickly understood by students. By utilizing data analysis and machine learning, the curriculum can be tailored to the needs of individual students, so that the learning experience becomes more personal and in-depth. AI also plays a role in increasing the accessibility of education, allowing remote areas to obtain quality learning materials through digital platforms. Meanwhile, Edu-Content makes it easier for students with attractive illustrations on every platform they use. In addition, the application of AI in the evaluation process can provide faster and more accurate feedback, helping educators identify areas that need improvement. Therefore, collaboration between the government, educational institutions, and the technology sector is very important to ensure that the implementation of AI in education can run sustainably and inclusively.